Construction and animation of realistic biceps 3D model - Poleszak, Sebastian; Kopniak, Piotr (Journal of Computer Sciences Institute, 2016)
The article concerns the development of three-dimensional model of how to build biceps human with the muscle looked and behaved realistically when animation. Data for animation are obtained by acquisition systems Motion - Motion Capture. Blender software v.2.76 was used to design a solid model. On this basis it is possible to carry out research on the analysis of the movement of the arm using data stored in BVH files.